Catalytic Cascade Dehydration-Etherification of Fructose into 5-Ethoxymethylfurfural with SO3H-Functionalized Polymers - Hu Li; Qiuyun Zhang; Song Yang (International Journal of Chemical Engineering)
A series of SO3H-functionalized polymers were prepared and employed as heterogeneous catalysts for one-pot transformation of fructose into 5-ethoxymethylfurfural (EMF) that is considered to be one of potential liquid biofuels. A high EMF yield of 72.8% could be obtained at 110°C for 10 h, and the polymeric acid catalysts could be recycled for five times without significant loss of catalytic performance.